Automated system for collection and differentiated evaluation of functional and special physical fitness of swimmers of different level of qualifications - Solopov, I. N.; Fomichenko, T. G.; Avdienko, V. B.; Bgantseva, I. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to justify and develop an automated system for collecting and differentiated assessment of functional and special physical fitness of swimmers of different skill levels.